Benign giant cell tumor of bone with pulmonary metastasis- report of two cases and review of literature - Nair, Geethu G.; G., Rajan; N. K., Supriya; P. P., Sathi (International Journal of Research in Medical Sciences, 2017)
Tumors that are metastasizing generally considered as malignant. But there are exceptions. Giant cell tumor of bone is well known for its potential to metastasize without sarcomatous transformation. Potential of benign GCT to metastasize was first reported by Jaffe et al in 1940. Prevalence of pulmonary metastasis in benign GCT is between 1-9%. Factors favoring metastasis include recurrence of tumor, surgical manipulation of initial bone tumor, location of femur etc. Peripheral or basilar portion of pulmonary parenchyma is involved commonly. Eventhough death reported in 16-25% of cases, overall it has a favorable prognosis. Surgical resection is preferred treatment for pulmonary metastasis. In the present study 2 case studies were done. In 1st study 18 year old female, known case of GCT Lt tibia, with history of curetting and cementing presented with pain and swelling at same site and pulmonary metastasis 1 year later. Biopsy from initial as well as recurrent tumor confirmed benign GCT without any features of atypia, mitosis or necrosis. Aspirate from pulmonary lesion showed osteoclastic giant cells. No treatment given to metastatic deposits and is asymptomatic even though size of pulmonary lesions is increasing. And in second study a 22 year old female, with past history of GCT referred to our institution for evaluation of lung lesion detected in X-ray. Patient underwent metastatectomy here and histopathology was similar to that of bone lesion. There was no evidence of sarcomatous transformation both in initial and recurrent lesion. Patient is asymptomatic other wise and doing well.